Self-Control of Online Game Users on Procrastination Behavior - Ubak, Arilla Ainda; Sholikha, Nisa’ Ayuna; Utami, Relawati Margi Tri; Zamroni, Zamroni; Kusumawati, Tri Mei (Proceedings Series of Educational Studies, 2024)
The use of online games has become a serious issue recently. Many students addicted to online games are unable to control, reduce, and stop playing. This addiction to online games leads to academic procrastination among students. Procrastination behavior is demonstrated through deliberate delay in completing assignments and even not doing them at all. Self-control has a strong influence in determining student procrastination. This study aims to identify the factors that trigger low self control among online game users, resulting in academic procrastination in students. The research method used in this study is qualitative, involving interviews and observations. Based on field observations, it was found that the tenth-grade students of SMAN 1 Tulungagung still do not have good self-control. They experience difficulties in managing time and restraining themselves from the temptation to play online games. Students' self-control is influenced by internal factors such as desires, interests, and awareness, as well as external factors such as peer environment, noise, an unconducive learning atmosphere, and lack of motivation from teachers regarding the learning material. Keywords: Online Game; Procrastination; Self-control